2021
DOI: 10.3390/jmmp5010019
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing Concept and Prototype for Train Component Using the FSW Process

Abstract: Friction stir welding (FSW) is a process originally developed for joining light materials, such as aluminum and magnesium, as an answer to their poor weldability by conventional fusion processes. In Colombia, the technique has been studied but its industrial implementation is uncommon, due to the high cost of specialized machinery and the unfamiliarity with the technique of local industries. This article presents an implementation case study of FSW on a 6082-aluminum alloy train component from Metro de Medellí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A lot of research has been conducted on process parameters and their effects on FSW aluminum alloys. The process parameters for welding are important for control-ling heat generation, plastic deformation, material flow, material mixing, metallurgy, strength, and reducing defects [12][13][14][15][16][17][18][19][20][21][22][23][24]. Recent studies on the optimal process parameters for aluminum welding found that rotation speed, welding speed, shoulder diameter per pin diameter ratio, tool geometry, and surface shoulder can cause increases or decreases in the strength and number of weld line defects [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of research has been conducted on process parameters and their effects on FSW aluminum alloys. The process parameters for welding are important for control-ling heat generation, plastic deformation, material flow, material mixing, metallurgy, strength, and reducing defects [12][13][14][15][16][17][18][19][20][21][22][23][24]. Recent studies on the optimal process parameters for aluminum welding found that rotation speed, welding speed, shoulder diameter per pin diameter ratio, tool geometry, and surface shoulder can cause increases or decreases in the strength and number of weld line defects [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Initial implementations of FSW relied on skilled research teams to develop a specific welding parameter for a fixed tool and set of boundary conditions to achieve a desired output. While this approach has yielded many successful applications of the process, starting as early as 1995 [2][3][4][5], this approach adds to the cost of development and makes transitions from machine to machine problematic at best [6]. The difficulties associated with the development of new welding parameters and transferring parameters to different equipment is largely based on the coupled nature of interactions within a friction stir weld.…”
Section: Why Temperature Control?mentioning
confidence: 99%
“…It shows excellent machinability, good welding performances, and high corrosion resistance [16]. AA6082 alloy is widely used in the high-speed train industry, such as profiles and carriage components [17,18]. Conventional welding methods might lead to the formation of defects due to the change of state, such as poor solidification and porosity in the nugget zone.…”
Section: Introductionmentioning
confidence: 99%